Measuring reading behavior in large-scale assessments and surveys - Locher, Franziska Maria; Philipp, Maik (Frontiers in Psychology, 2023)
Large amounts of studies have shown that reading behavior is an important aspect for the development of students’ reading skills. The construct reading behavior as examined in large-scale assessments and surveys within the field of empirical educational research is operationalized through a wide range of reading and reading-related aspects (e.g., reading time, reading frequency, print exposure, reading engagement, book genre preferences, knowledge of authors or book titles) and a broad array of measurement methods are used. The approaches to measure the same variable – namely reading behavior – differ fundamentally from each other, while at the same time, a clear concept that would help to classify the used measurement instruments and to interpret them in relation to the superordinate construct of reading behavior is missing. Therefore, the present article aims to give an overview of methods to measure reading behavior within the context of large-scale assessments and surveys, and to discuss how they were implemented. Finally, we make some suggestions on how it might be possible to relate the applied measurement approaches to each other, especially in terms of their content and theoretical relationship to the overarching construct of reading behavior.